Optimizing treatment sequencing in multiple myeloma: a novel model to predict survival outcomes - Maria Teresa Petrucci; Sara Bringhen; Cristina Entrala Cerezo; João Mendes; Patrizio Armeni (Hematology)
Objective Patients with multiple myeloma (MM) typically require multiple regimens and become harder to treat with each line of treatment. Furthermore, there is a lack of direct comparative clinical trial data to guide effective treatment sequencing. A novel model is described comparing alternative MM treatment sequences to optimize patient outcomes.Methods The model compares treatment sequences and outcomes for adults with newly diagnosed transplant-eligible (TE) or transplant-ineligible (TIE) MM across four treatment lines (first-line [FL] to fourth-line [4L]). Inputs are derived from patient-level data from clinical trials and indirect treatment comparisons. We report a base case prediction using data representing clinical practice in Italy.Results For FL TE, overall survival (OS) and progression-free survival (PFS) were greatest for FL regimens containing daratumumab; OS ranged from 11.80–18.10 years. PFS ranged from 4.82–13.42 years (FL) to 0.66–6.03 years (second-line [2L]), 0.81–1.76 years (third-line [3L]), and 0.69–0.72 years (4L). For FL TIE, OS rates were greater for treatment sequences with FL daratumumab vs. sequences with either 2L or no daratumumab (OS ranging from 5.95–10.61 years). PFS was greatest for FL daratumumab regimens in the TIE group, with PFS ranging from 2.12–7.48 years (FL), 0.53–4.73 years (2L), 0.63–1.17 years (3L), and 0.42 years (4L).Discussion This novel model demonstrates that using the most effective treatment in FL optimizes treatment sequencing and clinical outcomes for patients.Conclusion The optimal MM treatment sequences begin with daratumumab-containing regimens in FL and improve outcomes compared with alternative sequences.